Evaluation of chronic hepatitis B patients receiving lamivudine: Single center experience - Yapar, Derya; Akdoğan, Özlem (Journal of Surgery and Medicine, 2022)
Background/Aim: Lamivudine (LAM), which has been used for the treatment of Chronic Hepatitis (CHB) infection for many years, is now provided for short-time use to immunosuppressive patients due to resistance. We aimed to evaluate the current state and pandemic period routine follow-ups in patients who still used LAM today due to treatment or prophylaxis in terms of virologic or serologic treatment response. Methods: In this retrospective cohort study, we included 33 patients who received LAM treatment or prophylaxis due to CHB. Evaluations included patients’ serologic results for Hepatitis B, platelet counts, comprehensive metabolic panel, HBV DNA levels, ultrasonographic (USG) evaluation of the liver, and the number and duration of outpatient visits between 01.01.2020 and 31.12.2021. Results: Of all the patients, 51.5% (n=17) were males, and the average age was 57.3 (12.3) years. The median LAM treatment duration was found 10 (2.58) years. The ratio of receiving LAM due to immunosuppressive therapy was 27.27% (n=9). Except for HBV DNA-negative patients or patients with no accessed results, the virologic response rate of patients was found 60.7% (n=20). Within the study period, while Anti-Hbe seroconversion was found 3.2% (n=1), Anti-Hbs seroconversion was found 6.5% (n=2). One patient whose virologic response was not obtained, received the treatment without any alterations in the regimens. While the number of outpatient follow-ups in the study period was found 1.94 (0.24) on average, the duration between follow-ups was found 13.82 (12.8) months. Conclusion: It is pleasing to obtain virologic response and Anti-HBs, Anti-HBe seroconversion in patients with low resistance profile who receive the LAM treatment. While watchful waiting is recommended for patients receiving long-term LAM treatment, our retrospective analysis showed that planned outpatient follow-ups for every three months was done in longer intervals. The treatment is not altered in one patient whose virologic response was not obtained because of inadequate number of follow-ups within the study period. Since monitoring without having prolonged follow-up durations due to the pandemic is of importance in terms of preventing complications, we believe that there is a need for further studies on this issue.